Anticomplementary activity of the microflora of the intestine in people who are overweight and cardiovascular pathology - Lytvynenko, O; Osolodchenko, T; Kuchma, I; Savchenko, U (Annals of Mechnikov's Institute, 2020)
One of the main factors of progression of obesity in the world is the change of the style of nutrition. In the last decade, studies have shown that a change in the dietary structure leads to changes in intestinal biocoenosis. It has been stated that fatty food increases the number of gram-negative bacteria. In turn, gram-negative bacteria, directly through lipopolysaccharide of the outer membrane may be triggers of slowly progressive systemic inflammation. Material & methods. 227 strains of microorganisms from patients with various degrees of obesity were the object of the research. Also, the 63 strains from the control group with normal weight were studied. Anticomplementary activity (ACA) of microorganisms was studied according to the "three-layer" method using complement in concentration of 5 - 10 - 20 hem.unit/mL and the indicator crop of E. coli SISC, N212, highly sensitive to the bactericidal action of the complement. Results & discussion. As a result of the study of ACA of microorganisms it was found that genus Candida spp possessed the most pronounced activity. Gram-negative bacteria, such as Enterobacter spp and E. coli also showed pronounced ACA. The strains from the control group had slightly lower index. E. coli also showed ACA in 100,0 % of cases at the concentration of the complement of 5 hem.unit/mL. But with increasing concentrations to 10 and 20 hem.unit/mL figures differ slightly. The genus Enterococcus spp. has also differences in the percentage of active strains. Thus, it was found that 10% of strains of the experimental group and 25,0 % of strains of the control group did not have the ACA. Strains of the experimental group inactivated the complement at the concentrations of 5, 10, 20 hem.unit/mL in 90,0 %, 72,5 % and 70,0 % of samples respectively, and strains of the control group inactivated the complement in 75,0 %, 31,25 % and 6,25 % respectively. The study found that lakto- and bifidobacteria have ACA in a small percentage of cases. Thus, 66,67 % of lactobacilli and 68,59 % of bifidobacteria did not have the ability to inactivate the compliment, but 33,33 % of lactobacilli and 31,48 % of bifidobacteria were able to inactivate the complement at the concentration of 5 hem.unit/mL. The percentage of strains that inactivated the complement at the concentration of 10 hem.unit/mL was 20,83 % of lactobacilli and 11,1 % of bifidobacteria. ACA was absent in 80,95 % of lactobacilli from people with obesity without comorbidity. In obese hypertension patients this percentage was 56,25 %, and if the patient had IHD, the percentage decreased to 14,29 %. The percentage of bifidobacteria representatives which did not have the ability to inactivate the complement taken from people without cardiovascular pathology was 76,92 %. In people suffering from hypertensive disease, it dropped slightly to 58,82 %, and if people had IHD, it increased to 81,82%. Conclusion. 1. The representatives of intestinal microflora from people with different weight have different ability to inactivate the complement. The most likely reason for it is the changing nature of modern human nutrition. 2. Gram-negative intestinal microflora has the most distinct ability to inactivate the complement, which may indicate its role in the development of chronic inflammation of low-grade activity in patients with obesity. 3. Naturally, intestinal microflora in a small percentage (33,33 % of lacto- and 31,48 % of bifidobacteria) has the ability to inactivate the compliment. Increase of ACA of lactobacilli and decrease of ACA of bifidobacteria from patients with concomitant cardiovascular pathology can be explained by the influence of comorbidity on the biological properties of microflora as well as taking a large number of medicine by this group of patients for the treatment of hypertensive disease and ischemic heart disease, the influence of which on normal intestinal microflora is not sufficiently studied at present and requires a further study.